Hermeneutika dalam Interpretasi Undang-Undang No. 7 Tahun 2021: Menelusuri Perbedaan Makna Kenaikan PPN 12% - Arman, Zuhdi; ZAKI AZIZ, LEO (Yayasan Tri Edukasi Ilmiah, 2025)
In the 1945 Constitution of the Republic of Indonesia, the formulation of a law must undergo deliberation and mutual approval by the House of Representatives and the President. This is further elaborated in Law Number 12 of 2011 concerning the Formation of Legislation, specifically in Chapter IV on Legislative Planning, which states that a draft bill must go through the entire legislative process from inclusion in the national legislative program (Prolegnas) to discussion and ratification into positive law. Once a law has reached the ratification and implementation stage, it cannot be arbitrarily amended to adapt to changing times. In this context, hermeneutics the science of legal interpretation plays a crucial role, enabling the interpretation of legal provisions in a way that aligns with current societal needs, which may differ from those during the time the law was originally enacted. This scientific work employs a normative juridical research method, supported by both primary and secondary legal sources. The findings highlight the relationship between contemporary events and the necessity of adapting legal provisions, interpreted through the lens of phenomenological hermeneutics.